Kualifikasi Buku Siswa SD Kelas III Kurikulum 2013 - Wahyu Putri; Sudirman Sudirman; Baiq Niswatul Khair (Journal of Classroom Action Research, 2022)
Books play an important role in the lives of modern society. A lot of things are learned from books. The selection of books should pay more attention to the provisions contained in the preparation of the book. However, the reality in this era is that there are still many people who pour their writing by publishing textbooks without regard to the rules and standards of books. This can certainly be a source of problems in the learning process. Therefore, this study aims to find out the standard qualifications of content, language, and presentation in the book of class III students’ theme 1 growth and development of living things curriculum 2013 revision (2018). This research is a type of content analysis or content analysis that uses a qualitative approach. Data collection techniques use documentary study methods using assessment rubric instruments sourced from the National Education Standards Agency (BSNP). The results of this study show that the suitability of the student's book content standard, language and presentation of the book of class III students theme 1 growth and development of living beings curriculum 2013 revision (2018) as seen from the standard content, language and presentation obtained a percentage of: (1) conformity to the standard content is 91.66% which belongs to the category is very complete; (2) conformity to the language standard of 98.43% which belongs to the category of very complete; and (3) conformity to the presentation standard of 100% which falls into a very complete category